The Effect of Using Bigbox Application on Reading Comprehension of 5th Grade Elementary School Students - Rizki putri jasmine Siahaan; Deasy Yunita Siregar (Universitas Islam Negeri Palopo, 2025)
Reading comprehension is a crucial skill for elementary school students, yet many still face challenges due to limited vocabulary, low engagement, and the limitations of traditional teaching methods. With the advancement of digital technology, applications such as BigBox have been developed to provide interactive storybooks, vocabulary activities, and gamified exercises that foster student motivation and comprehension. This study aims to investigate the effectiveness of the BigBox application in improving the reading comprehension of 5th-grade elementary school students based on students’ perspectives. A qualitative case study design was employed, involving classroom observations, semi-structured interviews, focus group discussions, and student journals. The data was analyzed by thematic analysis. The findings indicate that BigBox supports students’ comprehension by enhancing engagement, motivation, and active participation compared to conventional reading practices. The interactive features of the application, including digital books, vocabulary exercises, and reading comprehension quizzes, played a crucial role in engaging students and improving their understanding of texts. The study highlights the potential of integrating digital applications like BigBox into elementary reading programs as a transformative approach to strengthening literacy development.